Plasma wakefield excitation providing homogeneous focusing of electron bunches - Maslov, V.I.; Onishchenko, I.N.; Yarovaya, I.P. (Вопросы атомной науки и техники, 2013)
Wakefield plasma lens, which focuses all relativistic electron bunches of the sequence identically and uniformly, are investigated analytically and by numerical simulation. The necessary conditions of such lens operation are the followings: length of the bunches is ξb=q(λ/2), q=1, 2, …(λ is the plasma wavelength), the distance between bunches is Δξ=pλ, p=1, 2, … All bunches have the same charge and the 1-st bunch has a half of this charge. It is shown that with the exception of 1-st bunch all other bunches are occurred in zero longitudinal wakefield and in uniform along bunch length focusing radial wakefield. In the case of inhomogeneous longitudinal distribution of electron bunch density the middle of bunches are focused slower in comparison with their edges.